2018
DOI: 10.1080/14786419.2018.1477150
|View full text |Cite
|
Sign up to set email alerts
|

Microbial hydroxylation and glycosidation of oleanolic acid by Circinella muscae and their anti-inflammatory activities

Abstract: Biotransformation of oleanolic acid (OA) by Circinella muscae AS 3.2695 was investigated. Nine hydroxylated and glycosylated metabolites (1-9) were obtained. Their structures were elucidated as 3β,7β-dihydroxyolean-12-en-28-oic acid (1), 3β,7β,21β-trihydroxyolean-12-en-28-oic acid (2), 3β,7α,21β-trihydroxyolean-12-en- 28-oic acid (3), 3β,7β,15α-trihydroxyolean-12-en-28-oic acid (4), 7β,15α-dihydroxy- 3-oxo-olean-12-en-28-oic acid (5), 7β-hydroxy-3-oxo-olean-12-en-28-oic acid (6), oleanolic acid-28-O-β-D-glucop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Xu et al (2020) have recently used the tandem biotransformation of oleanane-type pentacyclic triterpenoids using the fungal strain Rhizopus chinensis CICC 40335 and bacterial strains Bacillus subtilis ATCC 6633 and Streptomyces griseus ATCC 13273 [34]. The primary transformation of OA (0.2 g/L) using R. chinensis CICC 40335 occurred within 4 days by the formation of 7β,21β-dihydroxy-OA (54, 53.75%) previously obtained using the fungal strains Mucor rouxii NRRL 1894 [131] and Circinella muscae AS 3.2695 [15]. Further 4-day biotransformation of the obtained compound (54) led to the formation of 7β,21β-dihydroxy-olean-12-en-28-oic acid 3-O-β-D-glucopyranoside (108, 46.5%) using B. subtilis ATCC 6633 cells and a mixture of 7β,21β,29-trihydroxy-OA (109, 26.0%) and 3β,7β,21βtrihydroxy-olean-12-ene-28,29-dioic acid (110, 15.0%) using S. griseus ATCC 13273 cells [34].…”
Section: Bacterial Transformationmentioning
confidence: 92%
See 3 more Smart Citations
“…Xu et al (2020) have recently used the tandem biotransformation of oleanane-type pentacyclic triterpenoids using the fungal strain Rhizopus chinensis CICC 40335 and bacterial strains Bacillus subtilis ATCC 6633 and Streptomyces griseus ATCC 13273 [34]. The primary transformation of OA (0.2 g/L) using R. chinensis CICC 40335 occurred within 4 days by the formation of 7β,21β-dihydroxy-OA (54, 53.75%) previously obtained using the fungal strains Mucor rouxii NRRL 1894 [131] and Circinella muscae AS 3.2695 [15]. Further 4-day biotransformation of the obtained compound (54) led to the formation of 7β,21β-dihydroxy-olean-12-en-28-oic acid 3-O-β-D-glucopyranoside (108, 46.5%) using B. subtilis ATCC 6633 cells and a mixture of 7β,21β,29-trihydroxy-OA (109, 26.0%) and 3β,7β,21βtrihydroxy-olean-12-ene-28,29-dioic acid (110, 15.0%) using S. griseus ATCC 13273 cells [34].…”
Section: Bacterial Transformationmentioning
confidence: 92%
“…Furthermore, microbial conversion ensures specific modifications of triterpenic molecule sites that are either not modified or poorly modified by synthetic transformations [12]. Note that, among the known microbial biocatalysts, members of mycelial fungi are the most studied [13][14][15] whereas bacterial catalysts are only represented by a few gram-positive species [16][17][18][19][20]. The first papers on microbial transformation of triterpenoids were published in the 1960s [21].…”
Section: Distribution In Naturementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the selective glycosylation at C-28 was another main reaction type. It was also observed that the 3β-OH group was selectively dehydrogenated into carbonyl group [42].…”
Section: Microorganism Products Action Referencementioning
confidence: 99%